THE LESSON LEARNED FROM MENTAWAI TSUNAMI, OCTOBER 25th, 2010 - Mutmainah, Herdiana (Jurusan Perikanan dan Kelautan, 2025)
The Mentawai Tsunami, October 25th, 2010, was caused by collision between the Indian-Australian plate with the Eurasian plate that caused the fault in the Sunda subduction zone megathrust. Tsunami with magnitude 7.7 MW occurred at 21:42:22 pm which epicenter at 3.484oSL and 100.114oEL, 20.6 km depth in the Indian Ocean, 110 km from the North Pagai. Tsunami Mentawai, 2010 is started by an underwater earthquake and called as slow tsunami because the ground shaking is quite weak in long periods but produce great waves. Mentawai tsunami cesarean parameters are strike 325o, dip 11.62o and slip 101.4625o. This research aims to know the lesson learned of The Mentawai Tsunami. The impact is coastal degradation, i.e. loss of small islands, abrasion and mangrove degradation. The lessons learned are people should be aware of natural sign of tsunami, evacuate themselves to high places, avoid the inundation area, take the best decision based on situation. Tsunami mitigation must be implemented to save lives and minimize risks.Keywords: Mentawai Tsunami, tsunami impact, lesson learned.